2009
DOI: 10.1021/jp906087c
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chemical Substitution and Polymerization on the pKa Values of Sulfonic Acids

Abstract: The effects of ring substitution on the pK(a) value of benzenesulfonic acid (BSA) were investigated using a combined quantum mechanical and classical approach. Ring substitution with strong electron-withdrawing elements such as F, Cl, and Br is found to enhance the acidity of the BSA. More importantly, ring substitution with -NO(2) groups which form an extended conjugated pi-system with the benzene ring exhibits the strongest enhancement of the acidity. The effects of polymerization on the styrenesulfonic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 49 publications
(76 reference statements)
2
40
1
Order By: Relevance
“…[36] However, after incorporation into polymers, the p K a of acids have been shown to increase due to changes in the microenvironment that reduce the acidity of the acid groups. [37, 38] Based on the pH-responsive LCST curves, the p K a of βA and ACA are also increased to greater than 6.0 when they were incorporated in polymers (Figure 1A). Protonation of the acid groups at pH below their p K a increases the hydrophobicity of the polymer and shifts the LCST to a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[36] However, after incorporation into polymers, the p K a of acids have been shown to increase due to changes in the microenvironment that reduce the acidity of the acid groups. [37, 38] Based on the pH-responsive LCST curves, the p K a of βA and ACA are also increased to greater than 6.0 when they were incorporated in polymers (Figure 1A). Protonation of the acid groups at pH below their p K a increases the hydrophobicity of the polymer and shifts the LCST to a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was observed that poly(acrylic acid) brushes had an even higher pKa than that of the polymer in the bulk, due to the high osmotic pressure causing a strong condensation of counterions on polyelectrolyte chains. In a similar manner, the pKa of PSSNa brushes could be much higher than that of its sulfonic acid monomer (pKa = 1) . When the pH was below 3.5, PSSNa brushes became less ionized, which can promote the diffusion of R6G molecules inside less charged PSSNa brush layers.…”
Section: Diffusion Of Molecules Inside Polymer Brushesmentioning
confidence: 95%
“…These results are attributed to the lower pK a of oxidized sample (RS350-NS60) than those of primary biochar (RS350). The lower pK a of oxidized samples is mainly attributed to the nitro groups added to biochar surface (Dong et al 2009;Evanko and Dzombak 1998), as nitro groups can form an extended conjugated π system with the benzene ring, and exhibits strong enhancement of the acidity (Dong et al 2009;Evanko and Dzombak 1998). Because the carboxylic groups of oxidized samples were dissociated at relatively low pH values , the electrostatic bonding of Cd to biochars was reasonable.…”
Section: Effect Of Ph On Cadmium Adsorptionmentioning
confidence: 99%